Synchronization control of pulsatile ventricular assist devices by combination usage of different physiological signals. (1st October 2019) - Li, Xinghui; Zhong, Lunchao; Luo, Lin; Zhu, Shidong; Ni, Kai; Zhou, Qian; Yang, Bibo; Wang, Xiaohao
Abstract: Three different types of synchronous control methods based on physiological parameters, electrocardiogram (ECG) and fixed systole, ECG and aortic pressure, and ECG and phonocardiogram (PCG) were used to trigger a proposed intra-ventricular assist device (iVAD). The ECG, aortic pressure, and PCG were processed, respectively, and featured characteristics were extracted to trigger the iVAD-experimented in vitro circulation system in the laboratory. The data showed that all three types of synchronous control methods produced trigger pulses synchronously and that the iVAD synchronously beat with the native heart. The multi-cycle data demonstrated that the synchronous delay time of the proposed iVAD during systole and diastole was separately stabilized at a certain time. This study showed that the combination of three synchronization methods can be applied to the iVAD to improve the reliability of synchronization.